Математична модель датчика проковзування з реєстрацією поперечних складових магнітного поля чутливого елемента - Запорожець, Ю.М.; Кондратенко, Ю.П.; Шишкін, О.С. (Технічна електродинаміка, 2012)
New modification of slip displacement gage is offered based on measurement of the transverse constituents of magnetic field of permanent magnet applied in magnetosensitive system of the slip signal recording. Due to model of the magnet with the permanent value of magnetization analytical formulas are got for transversal constituents of its magnetic field in any point of space. Character of spatial distribution of magnetic field transversal constituents is analyzed depending on the parameters of sensing element construction and brought out the availability of such ratio ranges of these parameters, which assure linearity of the slip sensor static characteristics. The graphs of the spatial distribution of the transverse magnetic field components and examples of calculation of slip sensor static characteristic are brought.